Augmented Reality Training on Combat Sport: Improving the Quality of Physical Fitness and Technical Performance of Young Athletes - Meirizal Usra1; Irfan Benizar Lesmana; Kevin Octara; Wahyu Indra Bayu; Adela Badau; Asmadi Ishak; Edi Setiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to analyze the effects of augmented reality (AR) training in improving physical fitness and technical performance. An 11-week randomized controlled design was adopted in this study. This research involved sixty female athletes in Pencak Silat and Karate from Sriwijaya University (Indonesia). Participants were allocated into the experimental group, namely AR (Pencak silat: n=15, Karate: n=15) and control group (Pencak silat: n=15, Karate: n=15). Handgrip dynamometer, leg dynamometer test, medicine ball, standing long jump test, hexagon agility test, sit and reach test and multi stage test are used to measure physical fitness levels while the target punching test and target kick test are used to measure technical performance. The results of Student's t showed that there was a change in the mean value of AR (all, p < 0.05) and control only in MBT (p < 0.05) from baseline to final-test, ANOVA analysis we observed that there was an effect of Time on physical fitness (all, p < .001), there was a Group effect related to HDT (p < .001), MBT (p = 0.043), SART (p < .001), and MST (p < .001) and there was a Time * Group interaction related to HDT (p < .001), LDT ( p = 0.029), SLJT (p < .001), HAT ( p < .001), SART (p < .001), and MST (p < .001), there was an effect of Time on technical performance (all, p < .001), Group effect related to TPT (p = 0.004), and Time * Group interaction related to TPT (p = 0.001) and TKT (p < .001). Thus, we conclude that using AR for 11 weeks is an effective training method for improving the quality of physical fitness and technical performance of young athletes in combat sports.